Theoretical foundations of vocabulary work with preschool children - Makhmudov Khurshid Shukhratovich; Khudoykulova Aziza Anvar qizi; Abdugodirova Nozimahon Habibullo qizi (Genius Journals, 2025)
The essence of vocabulary work in a preschool educational organization is to systematize educational work aimed at helping children master words that are familiar or unfamiliar to them, but considered difficult for them, and improving their speech culture. Arming children with words that they learn with difficulty in their practice, do not recognize at all or at all, and pronounce in a distorted form requires considerable pedagogical efforts. Information on psychology, linguistics, physiology helps to determine the range of such words for children of different age levels.
Keywords: Vocabulary Work; Language Lexicon; Educator